2001
DOI: 10.1023/a:1013050423901
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning and the early development of PTSD

Abstract: Cross-sectional studies of chronic PTSD reveal deficits in verbal memory. We studied cognitive functioning and its relationship to current and subsequent PTSD severity during an early phase of trauma response. Thiry-eight participants with traumatic injuries and only posttrauma incident psychopathology were evaluated shortly after admission to a Level I Trauma Center Neuropsychological measures were obtained at baseline and assessment of PTSD and other psychiatric disorders was conducted at baseline and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…A substantial body of research has indicated that greater intellectual resources may protect against the development of PTSD (Breslau et al, 2006; Macklin et al, 1998; McNally & Shin, 1995; Vasterling, Brailey, Constans, Borges, & Sutker, 1997), and some authors have suggested that limited premorbid intellectual resources may be partially responsible for cognitive deficits in individuals with PTSD (Bustamante et al, 2001; Gilbertson et al, 2006). To address these concerns, we constructed difference scores for discrepancies in estimated IQ to determine whether patients poorly matched to a healthy comparison group on these variables varied systematically in neuropsychological performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial body of research has indicated that greater intellectual resources may protect against the development of PTSD (Breslau et al, 2006; Macklin et al, 1998; McNally & Shin, 1995; Vasterling, Brailey, Constans, Borges, & Sutker, 1997), and some authors have suggested that limited premorbid intellectual resources may be partially responsible for cognitive deficits in individuals with PTSD (Bustamante et al, 2001; Gilbertson et al, 2006). To address these concerns, we constructed difference scores for discrepancies in estimated IQ to determine whether patients poorly matched to a healthy comparison group on these variables varied systematically in neuropsychological performance.…”
Section: Discussionmentioning
confidence: 99%
“…Intelligence estimates have robust associations with neurocognitive performance. Therefore, it is possible that limited premorbid intellectual resources may be partially responsible for cognitive deficits in individuals with PTSD (Bustamante, Mellman, David, & Fins, 2001; Gilbertson et al, 2006). …”
Section: Neurocognitive Functioning In Ptsdmentioning
confidence: 99%
“…Most other researchers have found functional differences in language following trauma, though these are often attributed to other functional impairments. PTSD has been associated with performance decrements in word generation tasks for providing words that begin with a target letter (Bustamante, Mellman, & David, 2001;Gil et al, 1990;Koenen et al, 2001). There have been mixed results with categorical word generation tasks (Gil et al, 1990;Uddo et al, 1993).…”
Section: Languagementioning
confidence: 99%
“…However, memory disturbances are not limited to recall of the traumatic event, but extend to neutral information. Recall of verbal material (Bustamante, Mellman, David, & Fins, 2001;Johnsen & Asbjørnsen, 2008) and working memory performance have been shown to be particularly impaired (Morey et al, 2009;Vasterling et al, 2002). It has been hypothesized that the intrusive nature of trauma-related memories and goal-irrelevant environmental cues negatively affect cognitive processing in PTSD (McNally, 2006).…”
Section: Introductionmentioning
confidence: 99%